Memetakan Kemampuan Literasi Media Digital Ibu-Ibu Rumah Tangga di Desa Maguwoharja, Yogyakarta - Dewi Novianti; Siti Fatonah (Lembaga Penelitian dan Pengabdian Kepada Masyarakat UPN Veteran Yogyakarta, 2020)
The ability of digital media literacy housewife in the village of Maguwoharjo, Yogyakarta Indonesia is still low. Identifying media literacy skills for mothers needs to be done to provide media literacy education. This study uses methods; Interviews, focus group discussion, and media content analysis. The results of the study are mothers-housewives who use digital media only limited to entertainment, communication with family and people close, and little to the things that are knowledge. There are still mothers who are not able to apply smartphones or gadgets. They struggled to monitor the content that the kids had consumed. The role of mothers in child mentoring when interacting with the media is still very minimal. Many digital media applications are unknown and have not been optimal in assisting their children in consuming digital media. key words; Digital media literacy, housewives